Magnetic Circuit Design and Optimization Analysis of Cylindrical Magnetorheological Brake - Huang Jin; Wang Jian; Chen Song (Jixie chuandong)
According to the traditional excitation coil magnetorheological device,it is powered on for a long time to produce high temperature resulting in brake efficiency failure problems of MRF. A novel cylindrical magnetorheological device using permanent magnet instead of coil as magnetic source is designed. Aiming at the transmission device,the working principle of brake is analyzed,the magnetic circuit model is buit. The analysis of the brake magnetic circuit model is simulated by using ANSYS to verify the correctness of the theoretical model. The simulation results show that the addition of isolation ring can increase the strength of the magnetic field,but the magnetic field fluctuations. The magnetic field strength can be increased within a certain range of magnetic declination and without magnetic saturation phenomenon.